1984
DOI: 10.1111/j.1471-0528.1984.tb15086.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of progesterone and some of its metabolites including deoxycorticosterone after oral and parenteral administration

Abstract: Summary. Single 100‐mg doses of progesterone were given orally and as intramuscular injections t o four women during the follicular phase of the menstrual cycle. After oral administration serum levels of progesterone increased rapidly to reach luteal phase values (mean maximum level 55.6 nm) within 1–4 h and were still elevated after 12 h. The serum concentrations of 20α‐hydroxy‐4‐pregnen‐3‐one showed a similar pattern while there were only minor transient changes in 17α‐hydroxypro‐gesterone concentrations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…There was a great variability in bioavailability of pro gesterone following ingestion of micronized progesterone which is due to differences in the absorption rate and has also been observed in previous studies [10,[17][18][19], The present study did not reveal any significant effect of a single dose of 300 mg micronized progesterone ad ministered in the evening on cognitive performance pa rameters on the following morning in male volunteers. This is in line with a previous study in young female sub jects [10,11], in which pronounced effects were reported only at a dose exceeding 600 mg.…”
Section: Discussionsupporting
confidence: 35%
“…There was a great variability in bioavailability of pro gesterone following ingestion of micronized progesterone which is due to differences in the absorption rate and has also been observed in previous studies [10,[17][18][19], The present study did not reveal any significant effect of a single dose of 300 mg micronized progesterone ad ministered in the evening on cognitive performance pa rameters on the following morning in male volunteers. This is in line with a previous study in young female sub jects [10,11], in which pronounced effects were reported only at a dose exceeding 600 mg.…”
Section: Discussionsupporting
confidence: 35%
“…During the past decade, numerous studies have shown comparable efficacy between the vaginal progesterone gel and IM progesterone when used for luteal supplementation during IVF-ET [11,12,14,15]. IM progesterone produces supraphysiologic serum progesterone levels that are significantly higher than those achieved with vaginal progesterone gel [9,16,17]. However, the progesterone levels at the target tissue-the endometrium-are significantly higher with vaginal gel than with IM progesterone [9].…”
Section: Introductionmentioning
confidence: 97%
“…Around 95-98 % of progesterone in blood is protein-bound, with most of it bound to serum albumin. Oral administration increases plasma levels of progesterone metabolites, primarily of pregnandiol, pregnanolone (dihydroprogesterone), pregnandione, 20-αdihydroprogesterone and 17-OH-progesterone [6][7][8]. 5-α-hydroxysteroid dehydrogenase converts metabolic intermediates to allopregnanolone, an important neuroactive steroid [9,10].…”
mentioning
confidence: 99%